2022
DOI: 10.1002/alz.12913
|View full text |Cite
|
Sign up to set email alerts
|

TRIM25 mutation (p.C168*), coding for an E3 ubiquitin ligase, is a cause of early‐onset autosomal dominant dementia with amyloid load and parkinsonism

Estrella Gómez‐Tortosa,
Yalda Baradaran‐Heravi,
Lubina Dillen
et al.

Abstract: Introduction: Patients with familial early-onset dementia (EOD) pose a unique opportunity for gene identification studies. Methods: We present the phenotype and whole-exome sequencing (WES) study of an autosomal dominant EOD family. Candidate genes were examined in a set of dementia cases and controls (n = 3712). Western blotting was conducted of the wild-type and mutant protein of the final candidate. Results: Age at disease onset was 60 years (range 56 to 63). The phenotype comprised mixed amnestic and behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…CpG methylation on HERC5 gene, suggesting its downregulation is seen in late-onset AD cases, when compared with the normal controls [73]. A mutation in TRIM25 is associated with early-onset autosomal dominant dementia and amyloidogenesis [74]. Further, RNA-seq data suggests low abundance of HERC5 and TRIM25 in brain samples analysed from individuals with aging, dementia or with traumatic brain injury, when compared with healthy subjects [75].…”
Section: Discussionmentioning
confidence: 99%
“…CpG methylation on HERC5 gene, suggesting its downregulation is seen in late-onset AD cases, when compared with the normal controls [73]. A mutation in TRIM25 is associated with early-onset autosomal dominant dementia and amyloidogenesis [74]. Further, RNA-seq data suggests low abundance of HERC5 and TRIM25 in brain samples analysed from individuals with aging, dementia or with traumatic brain injury, when compared with healthy subjects [75].…”
Section: Discussionmentioning
confidence: 99%
“… 20 Previous study has shown that Trim25 , coding for an E3 ubiquitin ligase, is associated with AD and PD through a loss-of-function mechanism, suggesting its potential as a biomarker. 55 …”
Section: Discussionmentioning
confidence: 99%